The making of 'good citizens': German courses for migrants and refugees - Heinemann, Alisha M. B (Studies in the education of adults, 2017)
Newcomers to Austria and Germany are obliged to learn German, as both of the nation states define themselves as monolingual -- although millions of citizens speak more than one language. The demand to learn the national language is promoted by the shaky promise that it is an entrance ticket to the labour market and also a sine qua non to be respected by German and Austrian citizens. The main research questions of this qualitative study on language courses for migrants and refugees in Germany and Austria are as follows. Which normative knowledge is conveyed to students? How is it conveyed? How do students resist, and sometimes even subvert the (hidden) endeavours of the courses? Through participatory observation, interviews with teachers and a discourse analysis of the state accredited teaching materials, I demonstrate how Eurocentric norms are reproduced and stabilized. The first results highlight the reproduction of mainstream norms and the production of three different interwoven subject types: a) the economic subject who responds appropriately to the needs of a national neoliberal labour market; b) the submissive subject who agrees to norms and rules without the power to fully politically participate; c) the othered subject who forms the pleasing 'constitutive outside' of the national body.